(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
During Summer 1999 a tria! has been carried out in a citrus lemon orchard to test the side effects of Azadirachtin (OIKOS®, 150ml/hl c.p.) mixed with mineral paraffinic oil (Biolid E®, 500 gr/hl) and a surfactant (AG.N.®, 50 gr/hl c.p.) respectively, against the natural parasitoids of the citrus leafminer (CLM). The statistica! analysis results should not indicate substantial differences between the total percentage of parasitism observed in the treated and untreated plants. Nevertheless during the observations a percentage of 11,34 and of 16,67 of parasitoid larvae respectively, some days after the first and the second spray, showed terathological symptoms.